EVALUATION OF DISTRIBUTION PIPELINE NETWORK USING EPANET 2.0 PROGRAM IN KARANGSARI PERMAI HOUSING, SIANTAR MARTOBA DISTRICT PEMATANGSIANTAR CITY - Panjaitan, Hadi; Dingel, Jonathan; K Tarigan, Adrian; Setiawan, Ben; Florenta Butar-Butar, Diana (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
Clean water is a basic need for humans, so it is only natural that the clean water sector is given priority in handling and fulfilling it. PDAM as a regional clean water management company should be able to meet this need. With the existing treatment system and piping network system, PDAM is expected to be able to meet the clean water needs of the people in Pematangsiantar City. The purpose of this study was to find out whether it is necessary to increase water production to meet the current clean water needs of PDAM Tirtauli customers, to simulate clean water distribution pipelines in Pematangsiantar City using the EPANET 2.0 program, and to compare the simulation results of clean water distribution pipelines using the program. EPANET 2. 0 with the results of the distribution pipe network system planning for the current existing conditions. Based on the simulation results, the pressure value for the peak hours of water use is 0.2 kg/cm (2 m) for the lowest pressure, while the highest pressure is 2.19 kg/cm (21 m). In addition, a comparison of the pressure value from the simulation results was also carried out with the results of field measurements at Karangsari Permai Housing Complex. From this comparison, the pressure value obtained from the simulation results was 0.2 kg/cm (2 m), while the pressure value for field measurements carried out by the NRW PDAM Tirtauli team in this housing was 0.14 Kg/cm (1.4 m). The difference in pressure values was caused by the age factor. pipes, water leaks, and limited research data. Based on the simulation results, the pressure value for the peak hours of water use is 0.2 kg/cm (2 m) for the lowest pressure, while the highest pressure is 2.19 kg/cm (21 m). In addition, a comparison of the pressure value from the simulation results was also carried out with the results of field measurements at Karangsari Permai Housing Complex. From this comparison, the pressure value obtained from the simulation results was 0.2 kg/cm (2 m), while the pressure value for field measurements carried out by the NRW PDAM Tirtauli team in this housing was 0.14 Kg/cm (1.4 m). The difference in pressure values was caused by the age factor. pipes, water leaks, and limited research data. Based on the simulation results, the pressure value for the peak hours of water use is 0.2 kg/cm (2 m) for the lowest pressure, while the highest pressure is 2.19 kg/cm (21 m). In addition, a comparison of the pressure value from the simulation results was also carried out with the results of field measurements at Karangsari Permai Housing Complex. From this comparison, the pressure value obtained from the simulation results was 0.2 kg/cm (2 m), while the pressure value for field measurements carried out by the NRW PDAM Tirtauli team in this housing was 0.14 Kg/cm (1.4 m). The difference in pressure values was caused by the age factor. pipes, water leaks, and limited research data. In addition, a comparison of the pressure value from the simulation results was also carried out with the results of field measurements at Karangsari Permai Housing Complex. From this comparison, the pressure value obtained from the simulation results was 0.2 kg/cm (2 m), while the pressure value for field measurements carried out by the NRW PDAM Tirtauli team in this housing was 0.14 Kg/cm (1.4 m). The difference in pressure values was caused by the age factor. pipes, water leaks, and limited research data. In addition, a comparison of the pressure value from the simulation results was also carried out with the results of field measurements at Karangsari Permai Housing Complex. From this comparison, the pressure value obtained from the simulation results was 0.2 kg/cm (2 m), while the pressure value for field measurements carried out by the NRW PDAM Tirtauli team in this housing was 0.14 Kg/cm (1.4 m). The difference in pressure values was caused by the age factor. pipes, water leaks, and limited research data.